A Study of the Impact of Sustainability Reporting on Software Industries in India and How the Business Has Changed - Joshi, Manoj (Digital Repository of Theses - SSBM Geneva, 2025)
This research critically reviews the evolution, implementation, and impact of Sustainability encompassing Environmental, Social, and Governance abbreviated as ESG reporting within the Indian Software Industry (referred as Software Industry or IT industry/companies in this research). Sustainability reporting in India was a voluntary practice, which has now become an integral requirement due to rising stakeholder demands and international stakeholder pressures. IT companies in India have positively adopted advanced ESG practices based on global frameworks such as the Global Reporting Initiative (GRI), Sustainability Accounting Standards Board (SASB) now merged under International Financial Reporting Standards (IFRS), Task Force on Climate-related Financial Disclosures (TCFD), and the United Nations Sustainable Development Goals (UN SDGs) and now the current regulatory requirements such as Business Responsibility & Sustainability Reporting in India and ESRS in EU and similarly in other parts of the globe based on their global operations requirement. This study uses a mixed-method research methodology, combining quantitative data from ESG reports of selected Indian companies and surveys, qualitative insights derived from questionnaire surveys from industry professionals within India and outside India, and a literature review on ESG reporting in the Indian context and peers across the globe. The hypothesis of this research is that comprehensive ESG reporting significantly improves sustainability-related gains and gives a competitive advantage, positively influencing stakeholders and investment increase. The study reveals persistent challenges, primarily concerning inconsistent data quality and accuracy, significant costs involved in ESG implementation and the absence of standardized reporting frameworks, and the potential risk of greenwashing. The analysis shows ESG maturity varies within the sector, and companies have taken differing approaches in reporting formats (integrated versus standalone) and validation methods (Self-declaration vs third party) however, preference for third-party validation shows enhanced credibility. Results support the hypothesis, confirming that robust ESG practices yield substantial strategic and operational benefits. Recommendations derived from this research emphasize the necessity for increased thirdparty ESG assurance and the availability of standard reporting frameworks which will improve transparency, comparability, and accountability. The thesis concludes that integrated ESG reporting is essential, not only for regulatory compliance but as a critical driver of long-term business sustainability and competitive advantage in the global marketplace.